Epistemic Significance of Emotivism - Ajayi, Toluwalase (NIU Journal of Social Sciences, 2021)
This paper examines the epistemic significance of emotivism, emotivism is an important breakthrough in the exposition of ethics and its subject matter. Emotivism embraces a number of different views. The best known expression of the theory could be found in the writings of the American philosopher C.L.Stevenson, and it is with his version of emotivism and his ideas on the nature of moral judgements that we shall base our argument. The paper deploys the critical tool of academic philosophy to the epistemic significance of emotivism. While acknowledging the fact that emotivism has paved a new way for looking at ethical issues, the paper defends the thesis that by emphasizing the roles of reasons, Stevenson offers an account which, despite making attitudes the primary element of ethical language, it is compatible with the existence of ethical reasoning. Our moral opinions and the evidence we have for them, are analogous to the opinions and evidence we have concerning non moral matters, it is possible to know or be justified in believing moral propositions in the very same sense as factual propositions, and we have good reason to believe that some of our moral opinions are true. Keywords: C.L. Stevenson , Emotivism, Ethics, Moral judgment, Moral knowledge.